Anxiety and Startle Phenotypes in Glrb Spastic and Glra1 Spasmodic Mouse Mutants - Schaefer, Natascha; Signoret-Genest, Jérémy; von Collenberg, Cora R.; Wachter, Britta; Deckert, Jürgen; Tovote, Philip; Blum, Robert; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2020)
A GWAS study recently demonstrated single nucleotide polymorphisms (SNPs) in the human GLRB gene of individuals with a prevalence for agoraphobia. GLRB encodes the glycine receptor β subunit. The identified SNPs are localized within the gene flanking regions (3’ and 5’UTRs) and intronic regions. It was suggested that these nucleotide polymorphisms modify glycine receptor expression and phenotypic behavior in humans contributing to an anxiety phenotype as a mild form of hyperekplexia. Hyperekplexia is a human neuromotor disorder with massive startle phenotypes due to mutations in genes encoding glycine receptor subunits. GLRA1 mutations have been more commonly observed than GLRB mutations. If an anxiety phenotype contributes to the hyperekplexia disease pattern has not been investigated yet. Here, we compared two mouse models harboring either a mutation in the murine Glra1 or Glrb gene with regard to anxiety and startle phenotypes. Homozygous spasmodic animals carrying a Glra1 point mutation (alanine 52 to serine) displayed abnormally enhanced startle responses. Moreover, spasmodic mice exhibited significant changes in fear-related behaviors (freezing, rearing and time spent on back) analyzed during the startle paradigm, even in a neutral context. Spastic mice exhibit reduced expression levels of the full-length glycine receptor  subunit due to aberrant splicing of the Glrb gene. Heterozygous animals appear normal without an obvious behavioral phenotype and thus might reflect the human situation analyzed in the GWAS study on agoraphobia and startle. In contrast to spasmodic mice, heterozygous spastic animals revealed no startle phenotype in a neutral as well as a conditioning context. Other mechanisms such as a modulatory function of the glycine receptor  subunit within glycinergic circuits in neuronal networks important for fear and fear-related behavior may exist. Possibly, in human additional changes in fear and fear-related circuits either due to gene-gene interactions e.g. with GLRA1 genes or epigenetic factors are necessary to create the agoraphobia and in particular the startle phenotype.